Renminbi Internationalization: A Journey to Where?. Issue 6 (4th November 2013) - Bowles, Paul; Wang, Baotai
ABSTRACT: The renminbi is currently undergoing a process of internationalization which has raised fundamental questions about the evolution of the international monetary system and the dominance of the US dollar. In this article, we assess how far the renminbi has travelled down the internationalization road and analyse the possibilities for it challenging the role of the US dollar in the future. We utilize Cohen's (1971 ) taxonomy to document the current dimensions of renminbi internationalization. Looking forward, we briefly summarize three common approaches to analysing currency internationalization, and propose a new approach. We argue that renminbi internationalization should be seen as a response to crises, first the Asian financial crisis and then the global financial crisis. As such, we argue that current internationalization has been driven by short‐term problem solving rather than a coherent long‐term strategy. The current path of RMB internationalization is best described as one of 'currency normalization' rather than 'currency dominance'.